Peran Hukum dalam Memberikan Perlindungan terhadap Perempuan dari Tindak Kekerasan di Era Globalisasi - A. Reni Widyastuti (Fakultas Hukum Universitas Gadjah Mada, 2009)
Protection towards woman from violence is our responsibility as individual, society, law enforcer and government. Woman or a group of woman can file accusation to CEDAW committee (Convention on the Elimination of all forms of discrimination Against Women), concerning heavy infringement and systematic that in self or a woman group, done by person or country of CEDAW signatory countries. Law gives protection towards woman from act violence enforceable by: woman cognizance enhanced towards right and the duty; society cognizance enhanced about the important effort overcomes violence towards woman; law enforcer apparatus cognizance enhanced; aid enhanced and counseling toward victim; construction programmed enhanced toward victim and executants; increase character mass media; reconstruction of criminal justice system; and international coordination in crime tackling agreement towards women.